Understanding different levels of group functionality: activity systems analysis of an intercultural telecollaborative multilingual digital storytelling project. Issue 5 (4th July 2017) - Priego, Sabrina; Liaw, Meei-Ling
ABSTRACT: An Activity Theory framework has been increasingly applied for understanding the tension or contradictions in telecollaboration. However, to date, few researchers have applied it to the analysis of digital stories, and none of them, to our knowledge, have used it to analyze the co-creation of multilingual digital stories. In this study, we explore the different levels of group functionalities in a telecollaborative project by employing Activity Theory to look into the tensions and contradictions occurred during multilingual digital storytelling co-constructions. We also analyzed the strategies employed by intercultural collaborative group members to resolve these tensions or contradictions. This study involved pre-service French-as-a-second-language (FSL) teachers in Canada and university-level EFL students in Taiwan. Based on research findings, pedagogical implications for intercultural telecollaboration are discussed. Suggestions for future research are also provided.